(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
This article puts forward some recommendations to improve the quality of the content of vocational education, modernize teaching methods, approaches and techniques in universities and increase the effectiveness of control. According to the author, application and integration of these recommendations will potentially enhance learner-centered teaching, offer greater opportunities for monitoring and in the shortest possible time (without additional material investments) significantly increase the efficiency of the system of higher education in Armenia.